2006
DOI: 10.1242/jeb.02292
|View full text |Cite
|
Sign up to set email alerts
|

The cellular response to heat stress in the gobyGillichthys mirabilis: a cDNA microarray and protein-level analysis

Abstract: SUMMARY The cellular response to stress relies on the rapid induction of genes encoding proteins involved in preventing and repairing macromolecular damage incurred as a consequence of environmental insult. To increase our understanding of the scope of this response, a cDNA microarray, consisting of 9207 cDNA clones, was used to monitor gene expression changes in the gill and white muscle tissues of a eurythermic fish, Gillichthys mirabilis(Gobiidae) exposed to ecologically relevant heat stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
226
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(245 citation statements)
references
References 66 publications
(76 reference statements)
17
226
2
Order By: Relevance
“…Indeed, most of the ion-transport-related genes were induced in response to heat stress but repressed in response to hypo-osmotic salinity stress. Other transcriptomic studies of heat stress have reported similar patterns of induction among genes that encode ion transporters (Buckley et al, 2006;Gao et al, 2004). In contrast to the reciprocal responses that were observed among most of the genes in this set, one gene involved in redox balance and oxidative stress (i.e.…”
Section: Responses To Salinity Stress In Mytilus Trossulus Versus Mytmentioning
confidence: 49%
“…Indeed, most of the ion-transport-related genes were induced in response to heat stress but repressed in response to hypo-osmotic salinity stress. Other transcriptomic studies of heat stress have reported similar patterns of induction among genes that encode ion transporters (Buckley et al, 2006;Gao et al, 2004). In contrast to the reciprocal responses that were observed among most of the genes in this set, one gene involved in redox balance and oxidative stress (i.e.…”
Section: Responses To Salinity Stress In Mytilus Trossulus Versus Mytmentioning
confidence: 49%
“…Interestingly, mitophagy is believed to be part of a more complex response, the mitochondrial unfolded-protein response, which is a stress response triggered by the accumulation of unfolded or misfolded proteins in the mitochondrial matrix and subsequent activation of molecular chaperones such as heat shock protein 60 (Hsp60) and mitochondrial Hsp70 (Haynes et al, 2013;Jovaisaite et al, 2014). Even though little information is available about Hsp60 in fish (but see Buckley et al, 2006), it has been demonstrated that after acute heat stress (Currie et al, 2000;Deane and Woo, 2005) or during mild warming (Logan and Somero, 2011) the transcript abundance of Hsp70 is initially increased but then decreases with further acclimation (Currie et al, 2000;Deane and Woo, 2005). It is therefore possible that after the temperature was raised from 10 to 16°C on day 1 in the present study, alteration of cardiolipin leading to mitochondrial impairment resulted in the triggering of the mitochondrial unfolded-protein response and stimulation of mitophagy to re-establish the mitochondrial homeostasis after day 2.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of HS on transcriptional regulation of protein synthesis has been reported in several species (Buckley et al 2006;Liu et al 2013). Protein synthesis is regulated by transcriptional regulation, either by transcription factor binding or by changing the structure of chromatin by chromatin remodeling factors; the maintenance of chromatin structure is of vital importance for organismal homeostasis (Kokavec et al 2007), while transcriptional cofactors are required for activator-dependent or activator-regulated transcription and for transmitting regulatory signals between gene-specific activators and the transcriptional machinery (Thomas and Chiang 2006).…”
Section: Effect Of Heat Stress On Fertility Through Mapk Signaling Pamentioning
confidence: 99%